Potential Dietary Contributions From Rice and Wheat Flour Fortification in the Solomon Islands: Results From the 2012-2013 Household Income and Expenditure Survey. Issue 1 (March 2019) - Imhoff-Kunsch, Beth; Shakya, Iju; Namohunu, Salome Aroma Diatalau; Pitaboe, Anna; Wong, Pierre; Tsang, Becky L; Codling, Karen; Foley, Jessica; Pachón, Helena
Background: Solomon Islands (SI) mandated wheat flour fortification in 2010. Rice is a key staple food in SI, and its fortification may provide an opportunity to deliver additional micronutrients to the population. Objective: To determine whether fortified rice (proposed) and fortified wheat flour potentially benefit women of reproductive age (WRA). Methods: We analyzed data from the 2012-2013 Household Income and Expenditure Survey to quantify food purchases, which served as a proxy for food consumption. We accounted for varied household composition by using adult male equivalent (AME) adjustments. Results: Among 4478 households, 95.6% purchased rice and 86.6% purchased at least 1 food containing fortified wheat flour in the previous 14 days. Median apparent intake of rice among WRA was 205 g/d/AME. If fortified according to proposed standards, this apparent intake could result in the consumption of 12.3 mg iron/d, fulfilling 44% of the estimated average requirement (EAR), and 226 µg folic acid/d, satisfying 57% of World Health Organization's recommended intake of 400 µg/d. Overall, apparent rice consumption could fulfill 113%, 114%, and 131% of the EAR for WRA for zinc, thiamin, and niacin, respectively. Fortified wheat flour was consumed in much lower quantities, with an estimated apparent median intake of 22 g/d/AME among WRA and 78 g/d/AME among women in urban populations. Conclusions: The potential benefit of fortified wheat flour in SI is likely limited to urban populations. Apparent consumption of fortified rice in SI could contribute considerably to daily intake of iron, B vitamins including folic acid, and zinc among WRA.